2021
DOI: 10.1007/s10637-021-01191-6
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic impact of pneumonitis after durvalumab therapy in patients with locally advanced non-small cell lung cancer

Abstract: SummaryBackground. Prognostic data on Japanese patients receiving durvalumab after chemoradiotherapy (CRT) for locally advanced non-small cell lung cancer (LA-NSCLC) are insufficient. Whether pneumonitis has prognostic implications in patients with LA-NSCLC who have received durvalumab also remains unclear. Methods. We retrospectively assessed the data of 82 consecutive patients who had received durvalumab after CRT at our institution between May 2018 and August 2020. A multi-state model was used to establish … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the PACIFIC trial ( Antonia et al, 2017 ), the median age of patients was 64 years while in most of the real-world included studies the median age was higher than 64. In the studies of Sankar et al (2022) , Tsukita et al (2021) Nishimura et al (2022) , and LeClair et al (2022) , the median age the highest, at 69, 70, 69.5, and 69.8 years, respectively. This age range is much more reflective of the actual age of NSCLC patients in actual clinical practice.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the PACIFIC trial ( Antonia et al, 2017 ), the median age of patients was 64 years while in most of the real-world included studies the median age was higher than 64. In the studies of Sankar et al (2022) , Tsukita et al (2021) Nishimura et al (2022) , and LeClair et al (2022) , the median age the highest, at 69, 70, 69.5, and 69.8 years, respectively. This age range is much more reflective of the actual age of NSCLC patients in actual clinical practice.…”
Section: Discussionmentioning
confidence: 92%
“…Of them, 67 articles were selected for a full-text review and 41 were then excluded due to different reasons. Finally, a total of 26 articles corresponding to 23 studies were included in the review ( Girard et al, 2019 ; Girard et al, 2020 ; Girard et al, 2021 ; Faehling et al, 2020 ; Jain et al, 2020 ; Jegannathen, 2020 ; Jung et al, 2020 ; Miura et al, 2020 ; Noronha et al, 2020 ; Offin et al, 2020 ; Bruni et al, 2021 ; Desilets et al, 2021 ; Jazieh et al, 2021 ; Kartolo et al, 2021 ; Landman et al, 2021 ; Lau et al, 2021 ; McDonald et al, 2021 ; Taugner et al, 2021 ; Tsukita et al, 2021 ; Vrankar et al, 2021 ; Wang et al, 2021 ; Avrillon et al, 2022 ; LeClair et al, 2022 ; Nishimura et al, 2022 ; Riudavets et al, 2022 ; Sankar et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Severe (grade ≥ 3) pneumonitis was also more frequent in our cohort (9% versus 2.7%). There seems to be a large range of pneumonitis rates post durvalumab in the current literature, from 22 to 81% (Supplementary Table S1) [7][8][9][10][11][12][13][14][15][16][17]. A recent meta-analysis by Wang et al also demonstrated this large range of incidences (22-48%) [18].…”
Section: Discussionmentioning
confidence: 79%